Human resource management : local and global perspectives - Diamante, Melva M.; Ledesma-Tan, Genevieve (Quezon City, 2007)
The book focuses on how HR managers and professionals can develop, implement, and evaluate their programs and services to ensure workforce competence and the organization's effectiveness.
Keywords: Personnel management